Implementation of the TPM Method to Increase Production Machine Productivity at PT. Cemara Saringan Medan - Lbn Raja, Elisa; Azhar, Asbon Hendra (Marqcha Institute, 2025)
PT. Cemara Saringan Medan, a medium-scale manufacturer of palm oil filtration components, continues to experience frequent machine downtime and performance inefficiencies that disrupt production stability and increase operational costs. To address these challenges, this study aims to enhance machine reliability and productivity through the implementation of Total Productive Maintenance (TPM) integrated with a web-based monitoring system. Using a waterfall-based research methodology, the study involved data collection, preprocessing, TPM computation (availability, performance efficiency, and quality rate), OEE analysis, UML-based system design, application development, and black-box testing. The results show that the company’s production machines achieved an availability level of 89%, performance efficiency of 83%, and a product quality rate of 96%, indicating that productivity losses are primarily attributed to breakdown-related downtime and cycle-time inefficiencies rather than product defects. The integration of TPM with digital monitoring further demonstrates strong potential to enhance maintenance transparency, reduce human error, and support more responsive decision-making. These findings imply that adopting web-based TPM tools can significantly improve operational control and serve as a scalable foundation for predictive maintenance in medium-scale manufacturing environments.